2016
DOI: 10.4172/2168-9296.1000175
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Facilitate the Intercellular Communications in the Pathogenesis of Lung Injury

Abstract: Extracellular vesicles (EVs) are a group of heterogeneous, nano-sized structures surrounded by lipid bilayer membranes that are released by cells. Depending on their size and mechanisms of formation, EVs are often referred to as exosomes, microvesicles (MVs) and apoptotic bodies (AB). EVs are evolutionally conserved vesicles that mediate intercellular communications and cross-talk, via transferring proteins, lipids and nucleic acids. Accumulating evidence suggests that EVs exert essential physiological and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Whereas the release of MVs is continuous, and stimulated by a variety of cell stressor, ABs are only generated as a result of cell death. In contrast MVs and Exos are continuously released by live cells (7, 8) in either the absence or presence of noxious stimuli (9, 10). Recent studies have shown that both proteins and nucleic acids are differentially sorted into the three types of EVs reflecting their functional diversity (3, 9).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas the release of MVs is continuous, and stimulated by a variety of cell stressor, ABs are only generated as a result of cell death. In contrast MVs and Exos are continuously released by live cells (7, 8) in either the absence or presence of noxious stimuli (9, 10). Recent studies have shown that both proteins and nucleic acids are differentially sorted into the three types of EVs reflecting their functional diversity (3, 9).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence further suggest that in addition to EV surface antigens, EV can shuttle microRNAs (miRNAs) that may play an essential role in mediating intercellular communication (1113). It is now generally accepted that single miRNAs have diverse targets and can up- or down-regulate hundreds of genes (14), MVs and Exos therefore act in part as messengers in the coordination of innate immune responses to noxious stimuli (7, 9, 10). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, in parallel respiratory diseases, such as chronic lung diseases, epithelial derived exosomes have been shown to drive local inflammation through significant macrophage and neutrophil activation (25). Further, these events serve as crucial mediators of acute lung injury (26). Whether similar processes could be going on in OM pathophysiology remains mostly unexplored and is the impetus for our work, but neutrophilic inflammation appears to be key in OM disease development (9).…”
mentioning
confidence: 97%
“…The cells of the immune system communicate by different means such as soluble factors, cell surface molecules and extracellular vesicles (EV). Exosomes are nanosized cell-derived EVs that are known to play critical roles in intercellular communication [4]. Prior to the understanding of their immunological functions, they were considered as insignificant cell garbage bags.…”
Section: Introductionmentioning
confidence: 99%